SAT0029 Impact of glucocorticoids on sirtuin 1 expression and proinflammatory cytokine production in rats with adjuvant-induced arthritis. (12th June 2018) - Wendling, D.; Abbas, W.; Kumar, A.; Pasquereau, S.; Verhoeven, F.; Prati, C.; Demougeot, C.; Herbein, G.
Abstract : Background: Sirtuin 1 (SIRT1) is a class III histone deacetylase which could play a critical role in several biological functions including lifespan, stress, and inflammation. Objectives: Our main objective was to evaluate SIRT1 expression in peripheral blood mononuclear cells (PBMCs) isolated from rats with adjuvant induced arthritis (AIA) treated or not with low and high doses of glucocorticoids (GCs). Our second aim was to determine the production of proinflammatory cytokines such as tumour necrosis factor alpha (TNF), interleukin-1 beta (IL-1) and interleukin-6 (IL-6) in tissues (liver and spleen) of these rats, and to assess a potential correlation between SIRT1 expression and the production of cytokines in tissues of rats with AIA treated or not with low and high doses of glucocorticoids. Methods: We performed a study on rats with AIA treated with low and high doses of prednisolone or left untreated. The SIRT1 expression was quantified in PBMCs using western blotting. Levels of proinflammatory cytokines TNF, IL-1 and IL-6 were assessed in liver and spleen from rats with AIA treated with GCs or left untreated using an ELISA assay. Results: SIRT1 expression was increased in PBMCs isolated from rats with AIA treated with LD-GCs and HD-GCs compared to untreated animals. In culture, resveratrol enhanced the SIRT1 expression in PBMCs isolated from rats with AIA in a dose-dependent manner. We observed increased levels of TNF alpha in liver (correlated with SIRT1 expression) and decreased IL-6 levels in spleens (negatively correlated with SIRT1 expression) from rats with AIA treated with LD-GCs and HD-GCs compared to controls. Conclusions: SIRT1 expression is increased in PBMCs isolated from rats with AIA and treated with GCs parallel to decreased levels of IL-6 in spleen and increased levels of TNF in liver. This study shows that the SIRT 1 expression is measurable in circulating PBMCs of rats with AIA and is increased under GC treatment. The potential epigenetic effect of GCs on production of proinflammatory cytokines in tissues, namely liver and spleen, is also studied. Disclosure of Interest: None declared